Kvisoft Flipbook Maker-Assisted E-Modules to Foster Learning Motivation in Elementary School Students on the Topic of Changes in The Shape of the Earth - Putri Alya Diana; Zulherman (Jurnal Penelitian Pendidikan IPA, 2024)
Student motivation in learning IPAS (Natural and Social Sciences) subjects remains relatively low. This issue can be attributed to various factors, such as the limited utilization of learning resources and the lack of comprehensive content coverage. The purpose of this study is to create an electronic instructional module with the assistance of Kvisoft Flipbook Maker. The study used research and development (R&D) methodology, explicitly incorporating the ADDIE model. The participants were subject content experts, media experts, language experts, and 96 fifth-grade elementary school students. Data collection methods consist of observations and assessments. Expert evaluations were conducted utilizing questionnaires, whereas students were administered with Pre-test and Post-test assessments. Data analysis was performed using quantitative descriptive techniques. The evaluation results from media experts indicated a 77% feasibility score, while material experts scored 93% and language experts scored 100%, signifying high feasibility. The findings suggest that implementing E-Modules positively impacts student performance, as evidenced by improved evaluation outcomes following integrating of the Kvisoft Flipbook Maker-assisted electronic module. This research underscores the significant role of technology in boosting elementary school students' motivation.